The Emergence of Organizational Forms: A Community Ecology Approach - Ruef, Martin (The American journal of sociology, 2000)
Ruef introduces a new ecological approach to the study of form emergence based on the notion of an organizational community--a bounded set of forms with related identities. Applying the approach to 48 organizational forms in the health care sector, the study suggests that the development of novel forms is affected by the positioning of their identities with respect to existing form identities in the community, by the aggregate density and size of organizations matching those existing identities, and by the amount of attention directed at identity attributes by sector participants.